Graphene oxide as a multi-functional additive for compatilizer, enhancer, and barrier in ethylene vinyl alcohol copolymer/aramid pulp composites. Issue 7 (6th February 2023) - Yang, Xuyu; Ye, Yingying; Liu, Jiayan; Liu, Weijun; Xiong, Xianqiang; He, Zhicai
Abstract : To improve the thermal, mechanical, and barrier properties of ethylene vinyl alcohol copolymer (EVOH)/aramid pulp (AP), graphene oxide (GO) was used as a compatilizer, enhancer, and barrier to fabricate EVOH-based composites. Abstract : To improve the thermal, mechanical, and barrier properties of ethylene vinyl alcohol copolymer (EVOH)/aramid pulp (AP), graphene oxide (GO) was used as a compatilizer, enhancer, and barrier to fabricate EVOH-based composites. The results showed that graphene oxide serves as an ideal compatilizer to reinforce the interfacial action between the EVOH matrix and aramid pulp. The EVOH/AP/GO composite presented the best combination of thermal stability, tensile strength, oxygen barrier, and heat deformation temperature by adding only 1 wt% graphene oxide, compared to those of pure EVOH. Moreover, both scanning electron microscopy (SEM) and polarized optical microscopy (POM) photographs demonstrated that the aramid pulp dispersed homogeneously into the EVOH resin with the addition of 1 wt% graphene oxide. Our work provides a novel and facile way for producing a prominent EVOH-based composite, which can be potentially used in packaging fields in the future.